Photo-controlled host–guest interaction as a new strategy to improve the preparation of "breathing" hollow polymer nanospheres for controlled drug delivery. Issue 43 (1st October 2015) - Zhang, Haitao; Tian, Wei; Suo, Rongtian; Yue, Yang; Fan, Xiaodong; Yang, Zhen; Li, Hui; Zhang, Wanbin; Bai, Yang
Abstract : Photo-controlled host–guest interaction is used to improve the core removal method for preparing "breathing" hollow nanospheres as drug delivery. Abstract : This paper presents the photo-controlled host–guest interaction between azobenzene and β-cyclodextrin as a new strategy to improve the method of core removal to prepare poly((itaconoyloxy)ethyl methacrylate)- block -poly( N -isopropylacrylamide)-based hollow nanospheres. This improved method for the preparation of hollow nanospheres is simple, environmentally friendly, and highly efficient. The resulting hollow nanospheres displayed a typical "breathing" behavior, which further induces the controlled release of doxorubicin hydrochloride. Cellular toxicity evaluation indicated that the hollow nanospheres possess good biocompatibility and can be used as promising doxorubicin hydrochloride carriers.